Draft Five Year Plan (1978-83) Part I - Outlines Union Territory of Delhi - Planning Commission (Planning Commission, 1978)
Planning in Delhi has not only to conform to National priorities but has to take into account special characteristics of Delhi such as urban development, improving the water -supply system, power, transport, education and medical facilities. In the first two Five year plans i.e. upto 1961, the problems of the territory could not be fully attended to as only an amount of 20 crores was spend i.e Rs. 5 crores in the First plan and crores in the Second Five Year Plan.
Planning Department, Delhi Administration